The Effect Of Educational Videos On The Waste Management Behavior Of First-Year Public Health Students At Payung Negeri Pekanbaru Institute Of Health In 2025 - Suryani, Suryani; Dona Martilova; Rahmat Saputra; Yursha Ruziana (IKES Payung Negeri Pekanbaru, 2025)
Waste remains a problem in the environment that continues to this day and must be addressed. The habit of littering, not recycling, and the lack of efforts to separate organic and un organic waste are major factors in the increase in waste volume. In addition, uneven environmental education exacerbates this condition, particularly among students. This study aims to determine the effect of educational videos on students' knowledge, attitudes, and behavior in waste management. This is a quantitative study using a quasi-experimental design, which is an experiment conducted on only one group with a one-group pre-test and post-test design measured by a pre-test conducted before the education and a post-test conducted after the education. The research was conducted at the Payung Negeri Pekanbaru Institute of Health with a sample of 40 first-year public health students at Payung Negeri Pekanbaru Institute of Health in 2025. The results of the statistical test using Wilcoxon showed a p-value = 0.000 (p<0.05), which means that there is an effect of providing educational videos on the knowledge, attitudes, and behaviors of waste management among first-year public health students at the Payung Negeri Pekanbaru Institute of Health